Pregnancy Health Literacy with Low Birth Weight Outcome in North Lombok Regency - Aulia Zahro Novitasari; Retna Siwi Padmawati; Yayi Suryo Prabandari (Berita Kedokteran Masyarakat (BKM), 2019)
Pregnancy health literacy with low birth weight outcome in North Lombok Regency: secondary data analysis of PEER Health SHS-LBW intervention studyPurpose: To analyze the relationship between pregnancy health literacy with low neonatal birth weight.Method: This study is a secondary data analysis of Peer Health study intervention in North Lombok using a nested case control design. This study was conducted on 289 women. The Case group consists of 73 women with LBW and the control group consists of 216 women with non-LBW. Analysis of bivariate results of the study using chi square.Results: The results of this study indicate an association of pregnancy health literacy with LBW. Lesser exposure to pregnancy health information (OR: 2.76, 95% CI: 1.55-4.95) as well as the lesser exposure to pregnancy care (OR: 2.07, 95% CI: 1.16-3.67) associated with the greater LBW birth.Conclusion: The improvement of pregnancy health literacy through health promotion for pregnant women can improve pregnancy health and prevent LBW.